Correlation Clinicopathological and Immunohistochemical Expression of Interleukin-6 (IL-6) in Keloid - Fairuz Fairuz; Erisca Utami; Hasna Dewi; Fitriyanti Fitriyanti; Miftahurrahma Miftahurrahma; Budi Justitia; Mara Imam Taufiq Siregar; Humaryanto Humaryanto (Indonesian Journal of Global Health Research, 2024)
IL-6 has been shown to enhance collagen synthesis and prolong the fibroblast proliferative phase, potentially contributing to uncontrolled keloid growth. However, despite its frequent mention in the literature as a crucial factor in keloid formation, studies specifically exploring the molecular mechanisms of IL-6 in fibroblast regulation and its interaction with other cytokines within keloid tissue remain limited. This study aims to further investigate the role of IL-6 in keloid matrix formation. This study is an analytical study conducted cross-sectionally. The samples used were patients diagnosed with keloids histopathologically based on microscopic criteria. Clinical data were taken from medical records and microscopic and immunohistochemical assessments using paraffin blocks available in the anatomical pathology laboratory of hospitals in Jambi city. There were 36 cases of keloids, aged between 12 and 42 years, mostly in women (66.7%), occurring in the trunk area (77.8%) 30 cases of recurrence (83.3%). We found 24 cases (77.8%) with strong IL-6 immunoexpression. There were 3 cases (8.3%) with no immunoexpression. There was a strong correlation between IL-6 immunoexpression and gender (p=0.03), age(0.04) and recurrence (p=0.02). The role of fibroblast cells is very important for the process of collagen formation in wound healing. The role of fibroblast cells is very important for the process of collagen formation in wound healing, where interleukin-6 in various theories and studies supports the process of collagen formation.